Perlidungan Hukum bagi Nasabah BMT (Baitul Maal wat Tamwil) Melalui Pembentukan LPS (Lembaga Penjamin Simpanan) - Aziz, Aufar Abdul (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2022)
The presence of BMTs as MFIs in Indonesia has colored economic growth as supporting funding for the small and medium enterprise sector. The status of BMT legal entities in Indonesia is the majority as cooperative legal entities, but there are also those that are PT legal entities, foundations, and not yet legal entities, in customer protection. There are two protection models, namely implicit deposit protection and explicit deposit protection. The implicit protection model is carried out through supervision of banks, while explicit supervision is carried out by the deposit insurance agency. Until now, the existence of LPS for BMT has not been known, although in Article 19 of Law no. 1 of 2013 stipulates that MFIs can also establish deposit insurance institutions (LPS). This research is a normative legal research that refers to various sources of primary legal materials and tertiary legal materials. The conclusion of this paper is, Legal protection for BMT customers is contained in Article 54 of Law no. 25 of 1992 regarding settlements in conditions where cooperatives experience dissolution. In addition to Law no. 1 of 2013 legal protection for customers is regulated in Article 24 and Article 25, and complaint services are regulated in Article 26. However, legal problems for BMTs are not only in explicit customer protection but in the form of BMT itself there is no regulation that stipulates that BMTs must what kind of legal entity? The government should have issued special rules for BMTs considering that BMTs are in principle different from cooperatives. BMT carries out two functions, namely collecting ZIS and running business in the micro sector.